Wintering pattern and floral biology of Hevea clones - Soman T A; Licy J; Nazeer M A; Sethuraj M R; Varghese Y A (Indian Journal of Natural Rubber Research, 1995)
Wintering pattern and floral biology of 25 clones of Hevea brasiliensis were studied in two consecutive years. Most of the modern high yielding clones were found to exhibit partial wintering. The intraclonal differences in the maturity of male and female flowers seem to play a major role in the prevalence of out crossing. So, while selecting parents for a polyclonal seed garden, care should also be taken to ensure that the peak periods of maturity of male and female flowers overlap as far as possible. Flowering in 1995 was accomplished two to six weeks in advance than during 1994. The continued drought and soil moisture stress experienced from December 1994 onwards might be the main factors which induced an early wintering and flowering in 1995. The early flowering during 1995 has triggered a second round of flowering during the same season, resulting in an extension of the flowering period.
Keywords: Agro-climatic stress; Agro-climatic stress; Anthesis; Anthesis; Floral biology; Floral biology; Hevea brasiliensis; Hevea brasiliensis; Pollen fertility; Pollen fertility